2015
DOI: 10.1038/micronano.2015.40
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale patterning of a metallic glass using sacrificial imprint lithography

Abstract: Bulk metallic glasses (BMGs) have been developed as a means to achieve durable multiscale, nanotextured surfaces with desirable properties dictated by topography for a multitude of applications. One barrier to this achievement is the lack of a bridging technique between macroscale thermoplastic forming and nanoimprint lithography, which arises from the difficulty and cost of generating controlled nanostructures on complex geometries using conventional top-down approaches. This difficulty is compounded by the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Nanomolds can be made out of anodic aluminum oxide (AAO), stainless steel, or even MGs. [12,47] Traditional TPF suffers from the unworkable flow resistance due to friction and nonwetting conditions at the template interface. [35] 3D-Ns are part of a larger group of electrodes referred to as one-body or binder-free electrodes (see Section 3.1).…”
Section: Top-down Approachmentioning
confidence: 99%
“…Nanomolds can be made out of anodic aluminum oxide (AAO), stainless steel, or even MGs. [12,47] Traditional TPF suffers from the unworkable flow resistance due to friction and nonwetting conditions at the template interface. [35] 3D-Ns are part of a larger group of electrodes referred to as one-body or binder-free electrodes (see Section 3.1).…”
Section: Top-down Approachmentioning
confidence: 99%
“…Sacrificial template techniques have been used in combination with metallic glasses and bioglasses. However, the structures produced are restricted to open structures with lamellae or fibrous/porous surface structures [41,42]. By combining room temperature glass structuring and sacrificial template replication, it is possible, for the very first time, to generate nearly arbitrarily-shaped freeform three-dimensional channels and hollow structures in fused silica glass.…”
Section: Sacrificial Template Replicationmentioning
confidence: 99%
“…Higuchi et al demonstrated the focusing effects of different designs of nonconductive stencil masks to change the size of nanoparticle deposits 19 . Osuji et al demonstrated that inverse masks of a grounded grid under a glass slide could lead to patterned deposits of polymer films 18 . More recently, Zhu and Chiarot demonstrated that the charging effects of ESD with near-field photoresist templates could result in focusing of towers of particles that greatly exceed the thickness of the mask 20 .…”
Section: Introductionmentioning
confidence: 99%